Competitiveness Analysis and Factors Affecting Indonesian Crude Palm Oil Exports in The International Market (Journal of Economic Education, 2022)
The aim of this research was to analyze the competitiveness of Indonesian crude palm oil in ten export destination countries in 2011-2019 using the Revealed Comparative Advantage and Export Product Dynamics methods and analyze the factors that affect export volume using panel data regression. The type of research used is quantitative research that uses secondary data. The results showed an average RCA > 1, which means that Indonesian palm oil in the ten main export destination countries has a comparative advantage or high competitiveness. Meanwhile, through the EPD analysis, China, Pakistan and Bangladesh are in the Rising Star position. In the United States, Egypt and Singapore are in the Falling Star position. Meanwhile, India, Spain, the Netherlands and Italy are in the Retreat position. In panel data analysis, the population of export destination countries, real GDP per capita of export destination countries, economic distance, and inflation of export destination countries affect the volume of Indonesian palm oil exports either simultaneously or partially.